2009
DOI: 10.1186/1471-2202-10-103
|View full text |Cite
|
Sign up to set email alerts
|

Neurological and neurobehavioral assessment of experimental subarachnoid hemorrhage

Abstract: About 50% of humans with aneurysmal subarachnoid hemorrhage (SAH) die and many survivors have neurological and neurobehavioral dysfunction. Animal studies usually focused on cerebral vasospasm and sometimes neuronal injury. The difference in endpoints may contribute to lack of translation of treatments effective in animals to humans. We reviewed prior animal studies of SAH to determine what neurological and neurobehavioral endpoints had been used, whether they differentiated between appropriate controls and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 108 publications
3
79
0
Order By: Relevance
“…5 Neurological scores were significantly correlated with body weight after SAH, as body weight gain and improving neurological scores have been shown to be codependent factors. 12 In addition, increased glutamate levels may lead to astrocyte dysfunction or apoptosis and decreased astrocyte activity might decrease glutamate uptake and enhance neuronal death. 1,22,23,25,32 As previously reported, 29 CVS is a major cause of mortality and morbidity; in the present study, we further demonstrated that the CVS was positively correlated with neuronal degeneration on Day 7 after SAH.…”
Section: Discussionmentioning
confidence: 99%
“…5 Neurological scores were significantly correlated with body weight after SAH, as body weight gain and improving neurological scores have been shown to be codependent factors. 12 In addition, increased glutamate levels may lead to astrocyte dysfunction or apoptosis and decreased astrocyte activity might decrease glutamate uptake and enhance neuronal death. 1,22,23,25,32 As previously reported, 29 CVS is a major cause of mortality and morbidity; in the present study, we further demonstrated that the CVS was positively correlated with neuronal degeneration on Day 7 after SAH.…”
Section: Discussionmentioning
confidence: 99%
“…The end points in human clinical trials are usually clinical outcome and delayed cerebral ischemia but neurological and functional examination after experimental SAH is still uncommonly used (Jeon et al, 2009;Takata et al, 2008). There is some evidence that reduction of angiographic vasospasm does not correlate with improved outcome in humans (Etminan et al, 2011;Macdonald, 2011;Macdonald et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The BBB breakdown develops even in the acute stage of SAH [66,67], and the indicator has been shown to be independent of influences, such as increased intracranial pressure or brain edema that may disrupt the BBB itself [48]. On the contrary, histological examination, including neuronal count, is usually used in models of SAH, which was induced by endovascular perforation of the internal carotid artery and is very rarely used in a model of SAH induced by the injection of blood into the cisterna magna [46]. In contrast to endovascular perforation, induction of SAH by the injection of blood into the cisterna magna is associated with neurological damage that is much more subtle.…”
Section: Discussionmentioning
confidence: 99%
“…Timing for the NSS assessment was based on observations that maximal neurological impairment is seen 24 h after SAH, becoming nonsignificant by 72 h [46]. The NSS of the rats was determined by 2 blinded observers, independent of one another Points were assigned for alterations of motor functions and behavior, such that the maximal score of 25 represents greatest neurological dysfunction, whereas a score of 0 indicates an intact neurological condition.…”
Section: Determination Of Neurological Performancementioning
confidence: 99%